3 Effect of Litter Size and Provision of Supplementary Liquid Milk Replacer During Lactation on Piglet Pre-Weaning Performance. (12th April 2022) - Willard, Naomi C; Moest, Nicole K; Vande Pol, Katherine D; Olivio, Alicia; Shull, Caleb M; McKilligan, Denny; Ellis, Michael
Abstract: Recent increases in litter size in commercial sows have been accompanied by higher pre-weaning mortality (PWM) and lower weaning weights. The objective was to determine effects of litter size and feeding liquid milk replacer during lactation (using an automated feeder) on piglet performance. A split-plot design was used with a 2x2 factorial arrangement of treatments: Milk Replacer (MR; main plot; Unsupplemented vs. Supplemented); Litter Size [LS; sub-plot; Low (2 piglets less than functional teat number) vs. High (2 piglets greater than functional teat number)]. Cross-fostering was carried out at 24 h after birth to create treatment litters with similar gender ratio, proportion of cross-fostered piglets, and average and CV of birth weight. Milk replacer was available from 24 h after birth to weaning. Piglets were weighed on d 1 and 20 (weaning) after birth; all PWM was recorded. Growth data were analyzed using PROC MIXED of SAS; PWM data were analyzed using PROC GLIMMIX. Models accounted for fixed effects of MR, LS, the interaction, and random effects of replicate and replicate by MR interaction. There were no MR by LS interactions ( P > 0.05) for any measurement. Supplemented compared with Unsupplemented litters had similar ( P > 0.05) litter size at weaning and PWM, but greater ( P < 0.05) average piglet and total litter weaning weight (Table 1). The High LS treatment had greater ( P < 0.05) litter size and total litter weight at d 1 and weaning, but higher ( P < 0.05) PWM and lower ( P < 0.05) average piglet weaning weight. In conclusion, supplementing piglets with liquid milk replacer increased weaning weight with no effect on PWM, and increasing litter size above sow teat number had negative effects on both PWM and piglet weaning weight.